The Spiritual Level of Love on The Poetry “Wanita Cantik Sekali di Multazam” By A. Mustofa Bisri - Wachid B.S., Abdul; Kim Young Soo (Hikmatuna : Journal for Integrative Islamic Studies, 2021)
This article aims to reveal the concept of love and spiritual level according to A. Musthofa Bisri. In revealing this concept, this article uses the poem A Beautiful Woman in Multazam by A. Musthafa Bisri as the object of research. The selection of the poem "Women is Beautiful in Multazam" is based on thematic considerations of longing and love for God, whose witness is real to women. Love and spiritual level in poetry use symbols of "love" and "longing" in the procession of human relationship with God which is different from the use of symbols in previous poems. This research is a literature review using a historical approach, especially the history of thought and Sufism, as well as the intertextual theory of a literary work from Julia Kristeva. For A. Musthofa Bisri, love has a close relationship with the two names of Allah, namely the Most Merciful (al-Rahman) and the Most Merciful (al-Rahim), both words come from the word "rahmah", compassion and there is a relationship that cause spiritual conditions to the spiritual level, namely tahlīl, tahlīl, tasbih, taḥmīd, takbīr, istigfār, syukr, khauf, rajā’, and tawakkul.